Patogenisitas Rhizoctonia solani setelah Penyimpanan pada Substrat Berbeda - Nursamsi Pusposendjojo (Universitas Gadjah Mada, 1999)
Rhizoctonia solani Kühn is a polyphagus fungus causing damping off on nurseries. The fungus develops a resistant structure on plant debris in the form of sclerotium. The sclerotium is the major inoculum for next crops. Evidence indicated that viability and pathogenicity of the inoculum were affected by type of substrate in which the inoculum survived and by length of resting period. Rice straw appeared to be a better substrate for R. solani survival than that of soil. All seedlings planted on soil inoculated with inoculum from rice straw showed greater disease intensity, earlier symptom development, and more growth retardation than those of being inoculated with inoculum from soil.